Li‐S Battery Analyzed by UV/Vis in Operando Mode. Issue 7 (7th June 2013) - Patel, Manu U. M.; Demir‐Cakan, Rezan; Morcrette, Mathieu; Tarascon, Jean‐Marie; Gaberscek, Miran; Dominko, Robert
<x xml:space="preserve">Abstract</x> Battery watch: UV/Vis spectrophotometry is demonstrated as a powerful analytical method for the in situ study of polysulfides. Through the interactions that occur between different chain‐length polysulfide molecules and the UV/Vis radiation, quantitative and qualitative determination of the polysulfides formed during Li–S battery operation can be achieved.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>